There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae) - Machado, Miguel; Teixeira, Renato Augusto; Lise, Arno Antonio (Zootaxa, 2018)
The Neotropical crab spider genera Tobias Simon, 1895 and Epicadus Simon, 1895 comprise species with remarkable somatic morphology and confounding taxonomic history. The results of our recent cladistic analysis corroborate and extend preceding taxonomic assumptions in showing that Tobias is a junior synonym of Epicadus. In the present paper the six species recently transferred from Tobias to Epicadus are redescribed. Two new species are described based on both males and females: Epicadus dimidiaster sp. nov. and Epicadus tigrinus sp. nov.; the male of Epicadus granulatus Banks, 1909 is described for the first time. The diagnosis of the genus is revised, an identification key is provided, and information on geographical distribution is updated. Epicadus now comprises eleven species.